Mastering Hyper-V Windows Server 2019 - Qasrawi, Adiy (Packt Publishing, 2018)
"In this video course, you will acquire the knowledge needed to plan, deploy, manage and upgrade your virtualization environments. You will be walked through the planning phase of your Hyper-V deployment, full deployment scenarios and most common set of advanced management features to keep your Hyper-V environment running reliably. By the end of the course, learn how to use the power of this hypervisor to simplify the infrastructure, reduce costs, improve productivity and better manage system resources."--Resource description page